2018
DOI: 10.3389/fnmol.2018.00294
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish Models of Neurodevelopmental Disorders: Past, Present, and Future

Abstract: Zebrafish are increasingly being utilized as a model system to investigate the function of the growing list of risk genes associated with neurodevelopmental disorders. This is due in large part to the unique features of zebrafish that make them an optimal system for this purpose, including rapid, external development of transparent embryos, which enable the direct visualization of the developing nervous system during early stages, large progenies, which provide considerable tractability for performing high-thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
136
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(139 citation statements)
references
References 124 publications
1
136
0
2
Order By: Relevance
“…27 The Danio rerio (zebrafish) is a fresh water specie of teleosteo fish native from Asia that has been used as a vertebrate model in the developmental biology, toxicology, and biomedical research, as well as in behavior studies. 28 This model has some advantages, such as easy handling, low maintenance cost compared with rodents, high reproduction rates, and large number of fertilized eggs. Further, zebrafish genome is well characterized with a homology around 70% when compared with human genome.…”
Section: Introductionmentioning
confidence: 99%
“…27 The Danio rerio (zebrafish) is a fresh water specie of teleosteo fish native from Asia that has been used as a vertebrate model in the developmental biology, toxicology, and biomedical research, as well as in behavior studies. 28 This model has some advantages, such as easy handling, low maintenance cost compared with rodents, high reproduction rates, and large number of fertilized eggs. Further, zebrafish genome is well characterized with a homology around 70% when compared with human genome.…”
Section: Introductionmentioning
confidence: 99%
“…To investigate the in vivo functions of PHETA1 and its close homolog PHETA2, we utilize zebrafish, an informative small vertebrate model organism for validating the pathogenicity of genes or alleles in human patients. This approach has offered valuable insight for clinicians into a broad range of genetic disorders, including neurodevelopmental disorders, ciliopathies, and Lowe syndrome (Coon et al, 2012;Oltrabella et al, 2015;Phillips and Westerfield, 2014; Disease Models & Mechanisms • DMM • Accepted manuscript Ramirez et al, 2012;Sakai et al, 2018;Song et al, 2016). Using histological, physiological, and behavioral analyses, we found that zebrafish pheta1 and pheta2 are required for endocytosis, ciliogenesis, and craniofacial development.…”
Section: Disease Models and Mechanisms • Dmm • Accepted Manuscriptmentioning
confidence: 90%
“…This motif directs OCRL specifically to clathrin-coated endocytic pits on the plasma membrane (Choudhury et al, 2009;Mao et al, 2009). PI(4,5)P2 is abundant at the plasma membrane and is involved in a wide variety of processes, including actin dynamics and endocytosis (Sasaki et al, 2009). Disrupting OCRL's phosphatase activity interferes with PI(4,5)P2 homeostasis, which is thought to contribute to the disease manifestations of Lowe syndrome (De Leo et al, 2016;Lowe, 2005;Vicinanza et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Zebrafish (Danio rerio) are freshwater teleost fish widely used to study genes important in human diseases and traits, including neurological disorders such as autism-spectrum disorder (ASD; see review from [1]), intellectual disability (ID), and epilepsy (see review from [2,3]).…”
Section: Introductionmentioning
confidence: 99%